Analysis of Smart Website Satisfaction Level with Importance Performance Analysis Method - Syaefulloh Syaefulloh; Asdelina Ritonga; Dian Putri Kriswayuni; Wari Fiyosa (Jurnal Ekonomi, 2022)
Riau Islamic University through SIMFOKOM (Information and Computing System), makes an application which is usually called Smart. Smart applications are web-based systems that are used for the online learning process, especially during the Covid-19 period. The purpose of this study was to determine the level of student satisfaction with the quality of the Smart website service. The quality of service used is the ServQual dimension. Sources of data used are primary data and secondary data. Primary data was obtained through a questionnaire. Secondary data is used to determine the sample. The sample used was selected randomly. Furthermore, it was analyzed using the consumer satisfaction index and importance performance analysis. The results showed that students were quite satisfied with the Smart website service. This is evidenced by the results of the average level of all indicators of 99.46%.